Performance enhancement of ultraviolet light emitting diode incorporating Al nanohole arrays. (11th September 2018) - Jiang, Jie'an; Guo, Wei; Xu, Houqiang; Yang, Zhenhai; Guo, Shiping; Xie, Weiping; Chee, Kuan W A; Zeng, Yuheng; Ye, Jichun
Abstract: Enhanced photoluminescence and improved internal quantum efficiency were demonstrated for ultraviolet light emitting diodes (UV-LEDs) with Al nanohole arrays deposited on the top surface. The effects of the thickness and periodicity of the plasmonic structures on the optical properties of UV-LEDs were studied, and an optimized nanohole array parameter was illustrated. Classical electrodynamic simulations showed that the radiated power is mostly concentrated along the edge of the Al nanohole arrays. Even though no obvious dip was observed in the transmission spectra associated with localized surface plasmon resonance, significant improvements in radiatiative recombination and light extraction efficiency were demonstrated, indicating the influence of Al nanohole arrays on the light emission control of UV-LEDs. It is anticipated that the enhanced luminescence can be obtained for various emitting wavelengths by directly adjusting the periodicity and morphology of the Al nanohole arrays and this new technology can alleviate crystal quality requirements of III-nitride thin films in the development of high efficiency UV optoelectronic devices.